2020
DOI: 10.1590/1980-549720200106
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados a maior risco de ocorrência de óbito por COVID-19: análise de sobrevivência com base em casos confirmados

Abstract: RESUMO: Objetivo: Realizar uma análise de sobrevivência de indivíduos diagnosticados com COVID-19 identificados pelos sistemas de informação em saúde, analisando os fatores associados ao maior risco de ocorrência de óbitos. Métodos: Análise de sobrevivência de indivíduos notificados por COVID-19 no estado do Rio Grande do Norte até o dia 24 de agosto de 2020, utilizando dados dos sistemas de informação em saúde. A variável dependente foi o tempo até a ocorrência do desfecho. As variáveis independentes fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
32

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 9 publications
4
10
0
32
Order By: Relevance
“…Among the 41 participants, 25 (61%) were male individuals, a fact that corroborates other studies, such as the studies conducted by Guan et al 21 and Galvão and Roncalli, 22 that observed a higher prevalence of the disease in male patients, in addition to a greater tendency to severe forms in this population.…”
Section: Discussionsupporting
confidence: 86%
“…Among the 41 participants, 25 (61%) were male individuals, a fact that corroborates other studies, such as the studies conducted by Guan et al 21 and Galvão and Roncalli, 22 that observed a higher prevalence of the disease in male patients, in addition to a greater tendency to severe forms in this population.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the univariate analysis are shown in Finally, it should be noted that, comparatively, the results of this survival analysis indicated values of probability of death for older adults that are lower than most studies found 11,13,33 . This is due to the fact that, unlike these studies, the present analysis did not include individuals aged ≤60.…”
Section: Figure 1-the Kaplan-meier Curves For Older Adult Mortality In the Northeast Region By Covid-19 According To Age Groups (Fig 1/a)mentioning
confidence: 67%
“…Em relação a tomografia computadorizada de tórax, os aspectos mais comuns são opacidades em vidro fosco e áreas de consolidação. 7 Em nosso paciente é possível fechar o diagnóstico de COVID devido os sintomas, RT-PCR positivo e padrão radiográfico sugestivo.…”
Section: Discussionunclassified